Rapamycin Alleviates the Symptoms of Multiple Sclerosis in Experimental Autoimmune Encephalomyelitis (EAE) Through Mediating the TAM-TLRs-SOCS Pathway - Li, Xiao-ling; Zhang, Bo; Liu, Wei; Sun, Meng-jiao; Zhang, Ya-lan; Liu, Hui; Wang, Man-xia (Frontiers in Neurology, 2020)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). Our research aimed to find an immunomodulatory therapy for MS. An experimental autoimmune encephalomyelitis (EAE) mouse model of MS was established induced with the syntheticmyelin oligodendrocyte glycoprotein peptide 35-55 (MOG35-55). Fifty C57BL/6 mice were randomly divided into the Normal group, EAE group, and Rapamycin group (EAE mice treated with three different doses of rapamycin). Hematoxylin and eosin staining and Weil myelin staining were performed on the brain tissues of mice after 21 days post-immunization. The protein expression of Gas6, Tyro3, Axl, Mer in paraventricular tissues were analyzed by immunohistochemistry. The mRNA and protein expression of Gas6, Tyro3, Axl, Mer, SOCS1, SOCS3, Toll-like receptor (TLR) 3 and TLR4 were detected by quantitative real-time PCR (qRT-PCR) and Western blot, respectively. An enzyme-linked immunosorbent assay (ELISA) was used to detect the secretion of the inflammatory factors IFN-γ and IL-17. Rapamycin treatment could ameliorate the behavior impairment in EAE mice induced by MOG35-55. The expression of Gas6, Tyro3, Axl, Mer, SOCS1, and SOCS3 were decreased in EAE mice at 21 days post-immunization, while the expression of Gas6, Tyro3, Axl, and Mer in rapamycin group was higher than that in EAE group. It was accompanied by an increase in anti-inflammatory proteins SOCS1 and SOCS3, a decrease in the inflammatory proteins TLR-3, TLR-4 and in the amount of IFN-γ, and IL-17. Rapamycin injection relieved the nerve function of and the loss of myelin sheath in the EAE mice, mainly through mediating the TAM-TLRs-SOCS signaling pathway to regulate natural immunity.